Comparison of Fasting Glucose with Post-Load Glucose Values and Glycated Hemoglobin for Prediction of Type 2 Diabetes: The Isfahan Diabetes Prevention Study - Janghorbani, Mohsen (SBDR - Society for Biomedical Diabetes Research, 2009)
OBJECTIVES: The aim of this study was to compare the ability of fasting plasma glucose (FPG), post-load plasma glucose values and glycated hemoglobin (HbA1c) to predict progression to diabetes in non-diabetic first-degree relatives (FDR) of patients with type 2 diabetes. METHODS: A total of 701 non-diabetic FDR of diabetic patients aged 20-70 years surveyed in 2003 to 2005 were followed until 2008 for the onset of type 2 diabetes mellitus. At baseline and at follow-ups, participants underwent a standard 75 g 2-hour oral glucose tolerance test (OGTT). Prediction of progression to type 2 diabetes was assessed by using area under the receiver-operating characteristic (ROC) curves based upon measurement of FPG, post-load glucose values and HbA1c. RESULTS: The incidence of type 2 diabetes was 33.9 per 1000 person-years in men and 48.6 in women. The incidence rates were 4.6, 50.7, and 99.7 per 1000 person-years in FDR with normal glucose tolerance, impaired fasting glucose and impaired glucose tolerance respectively. FPG value was a better predictor of progression to diabetes than any post-load glucose values or HbA1c. The areas under the ROC curves were 0.811 for fasting, 0.752 for 1/2-hour, 0.782 for 1-hour and 0.756 for 2-hour glucose vs. 0.634 for HbA1c (p < 0.001). CONCLUSIONS: FPG had more discriminatory power to distinguish between individuals at risk for diabetes and those who were not at risk than post-load glucose values during OGTT or HbA1c. Our findings support the American Diabetes Association recommendation of using FPG concentration to diagnose diabetes.